(untitled) (Research, Society and Development, 2022)
The use of activated carbon is evidenced by the increasing scope of carbon-based utilities in various industrial applications, including pharmaceutical antidotes, wastewater remediation, aquaculture, and toxin removal. Activated carbon produced from biomass residues by various processing methods and conditions is emerging as a promising adsorbent for ecosystem remediation, due to the extensive discharge of pollutants. The objective of the present research was to develop, from laboratory tests, the production of activated carbon using Brazil nut (Bertholletia excelsa Bonpl. Lecythidaceae) residues related to a drinking water treatment solution. The results of the tests indicated that the chestnut urchin residue has more advantage in burning and charcoal production compared to the nut shell residue, where it was possible to verify in the nut shell sample high rates of mass loss (20.92%) related to water absorption, which is not good for the production of any type of charcoal, in relation to the chestnut urchin sample, the mass loss rate was 5.21% related to water absorption, much lower than in the chestnut shell , which makes it visible in the production of coal and for consumption in any other branch.